Synthesie of BridgeHead-Fused 1,2,3-Triazolo[1,5-c]-1,2,4-Triazines: Novel Anti-inflammatory and Analgesic Therapeutic Systems. (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: bridgehead-fused1; 2; 3-trizolo[1; 5-c]1; 4-triazines; novel therapeutic systems; antiinflammatory; egg-albumin; oedema